CHOREOGRAPHIC FORM OF THE “KEMBANG PASESER” DANCE BY EDI POTTRE KONENG, SUMENEP DISTRICT - Zainollah, Nabilah Zinta Amaliya Faiqoh; Handayaningrum, Warih (Solah, 2025)
Kembang Paseser is a dance work by Edi Susanto that carries the theme of nature created in 2009. Kembang Paseser means the agility and alertness of coastal girls, which is identical with beauty while Pasisiran is the life of the people in Paseseran (on the seashore). This work was inspired by a coastal girl who was waiting for her father to come home from sailing happily, while her mother was waiting for her daughter to bring the results of sailing fish that were contained with kerre. The objectives of the research studied were: (1) Stages of Kembang Paseser Dance Choreography at the Pottre Koneng Art Studio, (2) Form of Kembang Paseser Dance. The research method used is descriptive qualitative. The results of this study indicate that the Kembang Paseser Dance is a Traditional Dance from the Pottre Koneng Art Studio, this dance takes the coastal concept where the movements use existing Dance movements that are further developed, namely from the Madura Paraben Dance. The choreography of the Kembang Paseser Dance includes several stages, namely Exploration, Improvisation, and Composition. The Kembang Paseser Dance has 20 types of movements and 11 floor patterns that can change according to the performance. Beautiful make-up using a bun decorated with 3-colored flowers (yellow, red, and green) and a combination of yellow, red, green eye shed colors that look fresh. The accompaniment to this dance is the Madura-an song in the form of a red "kerre" which is usually used for containers for sailing results. The conclusion in this study is that the Kembang Paseser Dance is a Traditional Dance from the Pottre Koneng Art Studio, this dance takes the coastal concept where the movements use the creativity of the choreographer and also the existing Dance movements are developed again, namely the Madura Paraben Dance.